ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN NASABAH LEMBAGA KEUANGAN BMT INSAN KAMIL SOLO - Widiastuti, Erni (Universitas Slamet Riyadi, 2016)
This research aims: 1) To determine and measure the impact of the effect of the physical evidence, reliability, responsiveness, assurance, and empathy partially on customer satisfaction financial institutions BMT Insan Kamil Solo. 2) To determine and measure the impact of the effect of the physical evidence, reliability, responsiveness, assurance and empathy simultaneously on customer satisfaction financial institutions BMT Insan Kamil Solo. Data needed in this research is the primary data in the form of respondents' assessment of the assessment dimensions of service quality and customer satisfaction. Data analysis techniques used in this study are: classical assumption test, multiple linear regression, t-test, F and coefficient of determination. The results of data analysis in this study can be concluded that: 1) There is the influence of the physical evidence, kendalan, responsiveness, assurance, and empathy partially on customer satisfaction institute noted that financial BMT Insan Kamil, 2) There is the influence of the physical evidence, reliability, responsiveness, assurance and empathy simultaneously on customer satisfaction noted that financial institutions Insan Kamil Solo. Judging from the magnitude of the coefficient of determination (adjusted R square) which has a positive value of 0,851, indicating that consumer satisfaction of customers of financial institutions BMT Insan Kamil Solo explained by physical evidence/tangibles, reliability/reliability, responsiveness/responsiveness, assurance/ assurance, and empathy/empathy of 85,1% and the remaining 14,9% describe their free variation that are not observed in this study.Keywords: Dimensions of Service Quality, Customer Satisfaction.PENDAHULUANBanyaknya lembaga keuangan yang ber-diri menjadikan konsumen dihadapkan pada banyak pilihan akan produk lembaga keuang-an yang ditawarkan. Bagi nasabah pelayanan yang bermutu sangat penting. Kualitas pela-yanan menjadi komponen utama karena produk-produk utama lembaga keuangan yaitu kredit dan pelayanan nasabah. Kedua komponen ini merupakan suatu penawaran yang tidak berbeda dan mudah ditiru. Oleh karena itu persaingan akan sangat dipengaruhi oleh kemampuan lembaga keuangan dalam memberikan pelayanan yang terbaik diban-dingkan pesaingnya (Sofyan, 2009: 273).Kualitas dan kepuasan pelanggan berka-itan erat. kualitas memberikan suatu dorongan kepada pelanggan untuk